Community Engagement for Coastal Abrasion Mitigation at Tanjung Beach, Rangsang Barat, Riau - Basriyah, Khusnul; Zumira, Aisyah; Sulisworo, Dwi (Jurnal Praktik Baik Pembelajaran Sekolah dan Pesantren, 2025)
This action aims to reduce the impact of abrasion on Tanjung Motong Beach, Permai Village. The 40 Days Challenge Team of SMAN 1 Rangsang Barat, together with the community around the beach and teachers, have planted mangrove trees, which are an effective and sustainable solution to reduce the impact of abrasion. This action consists of 5 ongoing weeks, the first week is conducting surveys and observations on Tanjung Motong Beach, the second week is collecting data on abrasion on Tanjung Motong Beach, and sowing mangrove seeds. Our team sowed 250 mangrove seeds from the api-api species, the third week provided education to residents living around Tanjung Motong Beach, conducted socialization and provided education to school residents, and interviewed several residents living around the coast of Tanjung Motong Beach. The fourth week, planting mangrove seedlings on Tanjung Motong Beach, Permai Village, the fifth week monitoring the development of mangrove seedlings that have been planted, monitoring small mangrove seedlings (not old enough to be planted on the beach), and evaluating the growth and development of mangrove seedlings that have been planted on Tanjung Motong Beach. The positive impact of planting mangrove trees not only helps prevent abrasion, but also contributes to improving the quality of the ecosystem, such as increasing biodiversity and reducing damage from sea waves.